2011
DOI: 10.1093/ntr/ntr168
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults' Perceptions About Established and Emerging Tobacco Products: Results From Eight Focus Groups

Abstract: Young adults are familiar with many tobacco products, but they convey little understanding of relative risks of new or trendy tobacco products, such as snus or hookah. Mindful of industry innovation, tobacco control advocates must continuously update prevention efforts, seeking new strategies to limit promotion, marketing, and use of new and conventional products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…Our study was consistent with others in finding that smokers’ believe switching from smoking to SLT represents trading in some risks for others,24 31 that they mistakenly believe SLT users have a higher risk of oral cancer than smokers,18 39 and that SLT risk perceptions are impacted by SLT's mode of delivery, that is, its prolonged direct contact with the mouth 18 24 32 33. Another qualitative study also found that this direct contact with the mouth made smokers feel like they would have less control over their nicotine and toxin exposure with SLT versus cigarettes, which they perceived they could better control by varying their inhalation levels and by exhaling and ‘blowing out’ toxins 24.…”
Section: Discussionsupporting
confidence: 90%
“…Our study was consistent with others in finding that smokers’ believe switching from smoking to SLT represents trading in some risks for others,24 31 that they mistakenly believe SLT users have a higher risk of oral cancer than smokers,18 39 and that SLT risk perceptions are impacted by SLT's mode of delivery, that is, its prolonged direct contact with the mouth 18 24 32 33. Another qualitative study also found that this direct contact with the mouth made smokers feel like they would have less control over their nicotine and toxin exposure with SLT versus cigarettes, which they perceived they could better control by varying their inhalation levels and by exhaling and ‘blowing out’ toxins 24.…”
Section: Discussionsupporting
confidence: 90%
“…A few recent studies have used qualitative methods to better understand consumer perceptions of a variety of tobacco products (Choi, Fabian, Mottey, Corbett, & Forster, 2012; Sami et al, 2012; Wray, Jupka, Berman, Zellin, & Vijaykumar, 2012). Qualitative methods such as focus groups and interviews are especially useful for examining reasons and cognitive processes underlying individual perceptions (Kreuger, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Despite knowledge of health risks associated with cigarettes, smokers in the study were not motivated to quit or interested in reducing harm by switching to ST (Sami et al, 2012). Meanwhile, findings from focus groups with young adults reveal that there is some confusion and disagreement about the relative risks of tobacco products (Choi et al, 2012; Wray et al, 2012). Some young adults viewed novel ST products such as snus and dissolvable tobacco as equally or more harmful as cigarettes; others perceived these products as less harmful than cigarettes because they are smokeless.…”
Section: Introductionmentioning
confidence: 99%
“…9 Importantly, users report that cigar products are appealing for reasons such as affordability and palatability, and these factors also predict their use. [10][11][12] The appeal of cigars may also be enhanced by users' belief that they are less lethal than cigarettes. Tobacco users have noted that the media warns only of the dangers of cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%